Association between triglyceride glucose index related parameters and obstructive sleep apnea hypopnea syndrome in a cross sectional study - Hansheng Xie; Jiefeng Huang; Menglan Chen; Yue Zhong; Jianming Zhao; Qichang Lin; Ningfang Lian (Scientific Reports)
Abstract The relationship between the Triglyceride-Glucose (TyG) index and Obstructive Sleep Apnea Hypopnea Syndrome (OSAHS) remains unclear. This study aimed to investigate the association between TyG index-related parameters (TyG, TyG-Body Mass Index (BMI), TyG-Waist Circumference (WC)) and OSAHS. Consecutive subjects referred to our sleep center were enrolled in this study and categorized into four groups based on the severity of OSAHS, as determined by the apnea-hypopnea index (AHI). Multivariate regression analysis was performed to identify independent risk factors associated with TyG index-related parameters in OSAHS. The study included 1250 participants, categorized into 114 without OSAHS, 212 with mild OSAHS, 257 with moderate OSAHS, and 667 with severe OSAHS. Significant differences were observed in fasting glucose levels, TyG, TyG-BMI, and TyG-WC across increasing severity of OSAHS. Multivariate regression showed that TyG-BMI and TyG-WC were independently associated with oxygen desaturation index (ODI), mean oxygen saturation (MSO2), and age (all p < 0.05). TyG was significantly associated with BMI, ODI, and sex (all p < 0.05). FPG was linked to BMI, age and MSO2, while insulin was associated with lowest oxygen saturation (LaSO2) and AHI (all p < 0.05). OSAHS-induced intermittent hypoxia is independently associated with increased TyG index-related parameters. These findings suggest that intermittent hypoxia may contribute to metabolic disturbances and insulin resistance, highlighting the need for further investigation into its clinical implications.